Penerapan model pembelajaran STAD berbantuan media AKTE guna meningkatkan hasil belajar siswa SD - Reina Rizky; Wawan Shokib Rondli; Santoso Santoso (Journal of Education, Cultural and Politics, 2026)
The learning process tends to be teacher-centered, the use of conventional methods makes students less active, and it is difficult to understand the values ​​​​contained in Pancasila causing low student learning outcomes. This condition requires learning innovations that can increase student active participation and understanding of the material. The purpose of this study is to describe the process of implementing the STAD (Student Teams Achievement Division) learning model assisted by AKTE media and to determine the extent of its improvement in learning outcomes. The results showed an average Pretest score of 63.75 and increased to 87.08 in the Posttest. The Normality Test showed that the data was normally distributed with a Pretest significance value of 0.173 and Posttest 0.107 > 0.05. The results of the Paired Sample T-test showed a significance value of 0.000 < 0.05 which means there is a significant difference between the Pretest and Posttest values. The N-Gain test table shows that the N-Gain score obtained was 0.7167 which is included in the moderate category. The N-gain percentage showed an average of 71.6720, which is interpreted as a fairly effective value. Therefore, it can be concluded that the Students Teams Achievement Division (STAD) learning model, supported by AKTE media, is effective in improving Pancasila Education learning outcomes.